Accelerating Technology Transition: Bridging the Valley of Death for Materials and Processes in Defense Systems - National Research Council (The National Academies Press, 2004)
Accelerating the transition of new technologies into systems and products will be crucial to the Department of Defenses development of a lighter, more flexible fighting force. Current long transition times-ten years or more is now typical-are attributed to the complexity of the process. To help meet these challenges, the Department of Defense asked the National Research Council to examine lessons learned from rapid technology applications by integrated design and manufacturing groups. This report presents the results of that study, which was based on a workshop held to explore these successful cases. Three key areas emerged: creating a culture for innovation and rapid technology transition; methodologies and approaches; and enabling tools and databases.
Keywords: Engineering and Technology; Industry and Labor

Track-Related Research Volume 3: Exothermic Welding of Heavy Electrical Cables to Rail -- Applicability of AREMA Track Recommended Practices for Transit Agencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's Transit Cooperative Research Program (TCRP) Report 71, volume 3: Track-Related Research Volume 3: Exothermic Welding of Heavy Electrical Cables to Rail -- Applicability of AREMA Track Recommended Practices for Transit Agencies evaluates current practices and possible improvements to methods of connecting heavy electrical cables to rail, and identifies areas where American Railway Engineering and Maintenance-of-Way Association (AREMA) recommended practices may not apply to transit operations. The report also identifies transit practices and components that are not addressed by AREMA recommended practices.
Keywords: Transportation and Infrastructure

Retooling Manufacturing: Bridging Design, Materials, and Production - National Research Council (The National Academies Press, 2004)
As the Department of Defense continues development of the future warrior system, the difficulty of moving rapidly from design to manufacturing for complex technologies is becoming a major concern. In particular, there are communication gaps between design and manufacturing that hinder rapid development of new products important for these future military developments. To help address those concerns, DOD asked the NRC to develop a framework for “bridging” these gaps through data management, modeling, and simulation. This report presents the results of this study. It provides a framework for virtual design and manufacturing and an assessment of the necessary tools; an analysis of the economic dimensions; an examination of barriers to virtual design and manufacturing in the DOD acquisition process; and a series of recommendations and research needs.
Keywords: Industry and Labor; Engineering and Technology

Materials Count: The Case for Material Flows Analysis - National Research Council (The National Academies Press, 2004)
The rising population and industrial growth place increasing strains on a variety of material and energy resources. Understanding how to make the most economically and environmentally efficient use of materials will require an understanding of the flow of materials from the time a material is extracted through processing, manufacturing, use, and its ultimate destination as a waste or reusable resource. Materials Count examines the usefulness of creating and maintaining material flow accounts for developing sound public policy, evaluates the technical basis for material flows analysis, assesses the current state of material flows information, and discusses who should have institutional responsibility for collecting, maintaining, and providing access to additional data for material flow accounts.
Keywords: Engineering and Technology; Industry and Labor

Science and Technology in Armenia: Toward a Knowledge-Based Economy - National Research Council (The National Academies Press, 2004)
An NRC ad hoc committee analyzed the current status and future development potential of Armenia's science and technology base, including human and infrastructural resources and research and educational capabilities. The committee identified those fields and institutions offering promising opportunities for contributing to economic and social development, and particularly institutions having unique and important capabilities, worthy of support from international financial institutions, private investment sources, and the Armenian and U.S. governments. The scope of the study included both pure and applied research as well as education in science-related fields. The committee's report addresses the existing capacity of state and private research institutions, higher education capabilities and trends, scientific funding sources, innovative investment models, relevant success stories, factors hindering development of the science sector, potential domestic Armenian customers for scientific results and products, and opportunities for regional scientific collaboration. An Armenian language version of the report is also available.
Keywords: Biology and Life Sciences; Industry and Labor

University Research Centers of Excellence for Homeland Security: A Summary Report of a Workshop - National Research Council (The National Academies Press, 2004)
In establishing the Department of Homeland Security (DHS), the Administration and Congress determined that science and technology should play a key role in the nation’s efforts to counter terrorism. Congress included an S&T directorate prominently in the DHS. Within that directorate, is the Office of University Programs, which is responsible for sponsoring a number of homeland security centers of excellence in the nation’s universities. These centers are to work on a spectrum of short- and long-range R&D and carry out crosscutting, multidisciplinary work on a variety of threats. To assist it in planning for these centers, TSA asked the NRC to hold a workshop to generate a broad range of ideas to draw on to help define the centers. This report presents the results of that workshop including the major ideas that emerged from the discussions.
Keywords: Conflict and Security Issues

Progress in Improving Project Management at the Department of Energy: 2003 Assessment - National Research Council (The National Academies Press, 2004)
In 1997, Congress, in the conference report, H.R. 105-271, to the FY1998 Energy and Water Development Appropriation Bill, directed the NRC to carry out a series of assessments of project management at the Department of Energy (DOE). This report, the 2003 Assessment, is the final one in that series. It presents an examination of DOE's progress in improving program management over the past three years including the Department's response to the recommendations of the previous assessments in this series. In addition to assessing DOE’s progress, the report also describes opportunities for further improvement and gives a prognosis for future developments.
Keywords: Energy and Energy Conservation; Transportation and Infrastructure

Maintaining High Scientific Quality at Los Alamos and Lawrence Livermore National Laboratories - National Research Council (The National Academies Press, 2004)
In recent years, there has been concern about security and operations management at Los Alamos and Lawrence Livermore National Laboratories (LANL and LLNL). As a result, Congress directed the Department of Energy (DOE) to hold open competitions for the management and operations (M&O) contracts for both LANL and LLNL. The quality of the scientific programs, however, did not appear to be a factor in that action, and the DOE's National Nuclear Security Administration (NNSA) wanted to ensure that the contract competitions preserve the high-quality science and engineering currently being performed at the labs. It asked the NRC to recommend how best the NNSA can create meaningful qualification and selection discriminators to help ensure world-class scientific quality is maintained in programs and activities at LANL and LLNL. This report presents those recommendations along with other important factors that should be considered in developing the request for proposals for the upcoming contract competition.
Keywords: Policy for Science and Technology; Environment and Environmental Studies

Thermally Sprayed Metal Coatings to Protect Steel Pilings: Final Report and Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 528: Thermally Sprayed Metal Coatings to Protect Steel Pilings: Final Report and Guide investigtes thermally sprayed metal coatings (TSMCs) and offers a guide for the application of TSMCs to protect steel pilings from corrosion.
Keywords: Transportation and Infrastructure

Future Needs in Deep Submergence Science: Occupied and Unoccupied Vehicles in Basic Ocean Research - National Research Council (The National Academies Press, 2004)
Deep-diving manned submersibles, such as Alvin, which gained worldwide fame when researchers used it to reach the wreck of the Titanic, have helped advance deep-ocean science. But many scholars in this field have noted that the number and capabilities of today's underwater vehicles no longer meet current scientific demands. At the same time, the relative value of manned and unmanned vehicles is often disputed. The report finds that new submersibles—both manned and unmanned—that are more capable than those in the current fleet are needed and would be of great value to the advancement of ocean research.
Keywords: Earth Sciences

Transmission Pipelines and Land Use: A Risk-Informed Approach -- Special Report 281 - Transportation Research Board (The National Academies Press, 2004)
TRB Special Report 281: Transmission Pipelines and Land Use: A Risk-Informed Approach calls upon the U.S. Department of Transportation's Office of Pipeline Safety in the Research and Special Programs Administration to work with stakeholders in developing risk-informed land use guidance for use by policy makers, planners, local officials, and the public.
Keywords: Transportation and Infrastructure; Environment and Environmental Studies; Engineering and Technology

Effects of Degraded Agent and Munitions Anomalies on Chemical Stockpile Disposal Operations - National Research Council (The National Academies Press, 2004)
The U.S. Army is in the process of destroying its entire stock of chemical weapons. To help with stockpile disposal, the Army’s Chemical Stockpile Disposal Program (CSDP), in 1987, asked the National Research Council (NRC) for scientific and technical advice. This report is one in a series of such prepared by the NRC over the last 16 years in response to that request. It presents an examination of the effect of leaking munitions (leakers) and other anomalies in the stored stockpile on the operation of the chemical agent disposal facilities. The report presents a discussion of potential causes of these anomalies, leaker tracking and analysis issues, risk implications of anomalies, and recommendations for monitoring and containing these anomalies during the remaining life of the stockpile.
Keywords: Environment and Environmental Studies

Forensic Analysis: Weighing Bullet Lead Evidence - National Research Council (The National Academies Press, 2004)
Since the 1960s, testimony by representatives of the Federal Bureau of Investigation in thousands of criminal cases has relied on evidence from Compositional Analysis of Bullet Lead (CABL), a forensic technique that compares the elemental composition of bullets found at a crime scene to the elemental composition of bullets found in a suspect's possession. Different from ballistics techniques that compare striations on the barrel of a gun to those on a recovered bullet, CABL is used when no gun is recovered or when bullets are too small or mangled to observe striations. Forensic Analysis: Weighing Bullet Lead Evidence assesses the scientific validity of CABL, finding that the FBI should use a different statistical analysis for the technique and that, given variations in bullet manufacturing processes, expert witnesses should make clear the very limited conclusions that CABL results can support. The report also recommends that the FBI take additional measures to ensure the validity of CABL results, which include improving documentation, publishing details, and improving on training and oversight.
Keywords: Behavioral and Social Sciences; Engineering and Technology

Biotechnology Research in an Age of Terrorism - National Research Council (The National Academies Press, 2004)
In recent years much has happened to justify an examination of biological research in light of national security concerns. The destructive application of biotechnology research includes activities such as spreading common pathogens or transforming them into even more lethal forms. Policymakers and the scientific community at large must put forth a vigorous and immediate response to this challenge. This new book by the National Research Council recommends that the government expand existing regulations and rely on self-governance by scientists rather than adopt intrusive new policies. One key recommendation of the report is that the government should not attempt to regulate scientific publishing but should trust scientists and journals to screen their papers for security risks, a task some journals have already taken up. With biological information and tools widely distributed, regulating only U.S. researchers would have little effect. A new International Forum on Biosecurity should encourage the adoption of similar measures around the world. Seven types of risky studies would require approval by the Institutional Biosafety Committees that already oversee recombinant DNA research at some 400 U.S. institutions. These "experiments of concern" include making an infectious agent more lethal and rendering vaccines powerless.
Keywords: Conflict and Security Issues; Policy for Science and Technology

Open Access and the Public Domain in Digital Data and Information for Science: Proceedings of an International Symposium - National Research Council (The National Academies Press, 2004)
This symposium, which was held on March 10-11, 2003, at UNESCO headquarters in Paris, brought together policy experts and managers from the government and academic sectors in both developed and developing countries to (1) describe the role, value, and limits that the public domain and open access to digital data and information have in the context of international research; (2) identify and analyze the various legal, economic, and technological pressures on the public domain in digital data and information, and their potential effects on international research; and (3) review the existing and proposed approaches for preserving and promoting the public domain and open access to scientific and technical data and information on a global basis, with particular attention to the needs of developing countries.
Keywords: Policy for Science and Technology; Computers and Information Technology